Excisional goniotomy with Kahook Dual Blade in a patient with glaucoma secondary to Transthyretin Amyloidosis - Natalie Brossard Barbosa (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To report for the first time the successful use of the Kahook Dual Blade excisional goniotomy technique in a patient with Transthyretin Amyloidosis. Patient and methods: The Kahook Dual Blade is a single use ab interno trabeculectomy device that removes the trabecular meshwork reducing aqueous humor outflow resistance. A patient with Transthyretin Amyloidosis underwent this procedure. Results: Ab interno goniotomy with Kahook Dual Blade was a successful surgical solution to reduce intraocular pressure in a patient with Transthyretin Amyloidosis secondary glaucoma controlling IOP in association with topical hypotensors for at least 6 months. Conclusions: Ab interno goniotomy with Kahook Dual Blade is a surgical option for this type of glaucoma, that treats the main site of aqueous outflow resistance in this pathology with the advantage of being minimally invasive.